Sobre moral, direito e democracia - Schumacher, Aluisio A. [UNESP] (CEDEC, 2004)
From the idea that morality and law imply a reference to the participant's viewpoint, the author explains that, under modern conditions, the latter compensates the frailty of the former. Based on Habermas' discourse theory, the author argues for an internal relationship between democracy and the rule of law. Firstly, because human rights and people's sovereignty are mutually implicated. Secondly, because the idea of the rule of law now involves the concept of communicative power: an overlapping and interconnection of communication forms based on arguments. From this second relationship, the author arrives at an understanding of democracy in which the source of legitimacy is no longer found in an individual's predetermined will but in the the very act of deliberating.

Da consideração de que moral e direito implicam uma referência ao ponto de vista do participante, o autor explica que o segundo compensa a fraqueza da primeira nas condições modernas. Apoiando-se na teoria do discurso de Habermas, ele argumenta por uma relação interna entre Estado de direito e democracia. Primeiro, porque direitos humanos e soberania popular se implicam mutuamente. Depois, porque a idéia de Estado de direito envolve agora o conceito de poder comunicativo: a sobreposição e interligação de formas de comunicação baseadas em argumentos. Desta segunda relação, o autor extrai uma concepção de democracia em que a fonte de legitimidade não é mais a vontade pré-determinada dos indivíduos, mas o próprio processo de deliberação.
On morality, law and democracy
Keywords: Normative theory; Jürgen Habermas; the rule of law and the public sphere; Teoria normativa; Jürgen Habermas; Estado de direito e esfera pública